Blasius Sudarsono’s Scientific Ventures through a Psychobiographical Lens: - - Rahmi, Rahmi (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACT This research examines Blasius Sudarsono’s scientific endeavors in librarianship and documentation from 1985 to 2020. Utilizing a detailed content analysis of his written works’ titles, the research delves into prevailing themes, reactions to sociocultural contexts, and the incorporation of cognitive psychology theories within his contributions. Through a qualitative approach and content analysis, we delved into Sudarsono’s diverse literary formats, finding that he predominantly conveyed his expertise through formal manuscripts and presentations, often leaning toward an Indonesian readership. The findings underscore Blasius’s profound dedication and expertise, especially concerning the pivotal role of libraries and documentation in the information landscape. Furthermore, his works manifest a keen awareness and adaptability to evolving social and cultural shifts and a comprehensive grasp of cognitive psychology principles. The conclusion accentuates the significance of libraries in ensuring seamless information access amid a fluid backdrop and offers insights for impending research in the digital age. His contributions have significantly shaped Indonesia’s librarianship and documentation fields, providing a foundation for emerging scholars and professionals, guiding best practices, and strategic adaptation in the ever-evolving era.     ABSTRAK Penelitian ini menelusuri kontribusi ilmiah Blasius Sudarsono dalam arena kepustakawanan dan dokumentasi selama periode 1985 hingga 2020. Melalui evaluasi mendalam terhadap judul publikasinya, studi ini menyoroti aspek tematik dominan, respons terhadap dinamika sosiokultural, serta penerapan prinsip-prinsip psikologi kognitif dalam tulisannya. Dengan metode kualitatif dan analisis isi, kami mengeksplorasi variasi format karya tulis Sudarsono. Hasil analisis menunjukkan dominasi karya-karya ilmiah dan presentasi formalnya, yang cenderung ditujukan untuk audiens Indonesia. Analisis ini menegaskan komitmen dan keahlian mendalam dari Blasius, khususnya dalam menyoroti keberadaan perpustakaan dan dokumentasi dalam dunia informasi. Karyanya mencerminkan kesadaran akut serta fleksibilitas terhadap transformasi sosial-budaya serta pemahaman mendalam terhadap teori psikologi kognitif. Kesimpulan studi menyoroti urgensi perpustakaan dalam memfasilitasi akses informasi yang efektif di era yang dinamis dan memberikan panduan untuk eksplorasi lebih lanjut di masa depan digital. Signifikansi karya Sudarsono telah membantu memberikan arah dan fondasi bagi praktisi dan akademisi muda di bidang kepustakawanan dan dokumentasi di Indonesia, memberikan pedoman dalam menjalankan inovasi dan adaptasi di zaman yang terus beradaptasi.